Melancholic Body, Mind without Memory, Multitude without Freedom: Three Aspects of Mutatio in Spinoza’s Philosophy - Benvenuto, Rodrigo Miguel (Tópicos, Revista de Filosofía, 2023)
The aim of this article is to analyze Spinoza’s thought from the possible articulations that arise from the notion of mutatio. Given the physical implications of this concept and the encounter between the simplest bodies and composite bodies, we establish three aspects that allow us to reflect on mutation, its differences with transition, and its link to conservation. First, we draw on an analysis of the melancholic disposition and how it affects body and mind using the example of King Saul, presented by Spinoza in the Tractatus Theologico-Politicus (I, 3). Secondly, we analyze mutatio through a particular case of amnesia suffered by a certain Spanish poet (in Ethics, IV, prop. 39, schol.). Finally, we consider mutatio in its political aspects and the problems that arise from the conservation and mutation of form. In all three cases we find a possibility of thinking of mutatio in consonance with the Spinozian project and the relational framework in which these fundamental concepts of his philosophy are developed.
Keywords: immanence; mutation; affects; politics; conservation